Values and global science: the epistemic and social relevance of geographic diversity (2025)
According to current philosophical proposals concerning the role of values in science, diversity is a necessary and desirable feature of our epistemic communities for managing and justifying the values that shape the production of knowledge. However, the discussion up until now has lacked a global perspective. It has primarily focused on abstract, national, or local contexts and mainly on scientific communities located in resource-rich environments. Accordingly, the normative tools at hand remain insufficient when we move on to explore matters of values and diversity on a global scale. In the dissertation, I explore how we can address the value-laden nature of global science, given the existing inequalities among scientific communities in different geographic locations. If indeed diversity is a promising avenue for managing the values that shape global scientific knowledge and encouraging a socially and epistemically just science, what sort of diversity is the one we should foster at this global level, and how? Here, I argue in favor of fostering geographic diversity. My main claim is that promoting non-oppressive collaborations among scientific communities in diverse locations and, consequently, in different material and social circumstances is a fruitful strategy to address the challenges posed by value-laden global science. With this in mind, first, I review the literature on values and diversity in science and argue that current philosophical frameworks omit this geographic dimension of diversity. Consequently, they do not offer normative recommendations for building a geographically diverse and non-oppressive global science. Furthermore, these proposals run the risk of being epistemically unjust towards scientific communities in low-and middle-income countries (LMICs). Second, I explain why remedying this gap is epistemically and socially relevant. I claim that scientific communities in LMICs suffer different forms of epistemic oppression within the structure of global science, and I point out the social and epistemic detrimental effects of this oppression. Finally, I attempt to outline a set of normative and ameliorative recommendations to counteract this epistemic oppression and foster geographic diversity in order to manage and address the values and social structures that shape global scientific knowledge.